Suppression of Specular Reflections by Metasurface with Engineered Nonuniform Distribution of Reflection Phase - Xin Mi Yang; Ge Lan Jiang; Xue Guan Liu; Cheng Xiang Weng (International Journal of Antennas and Propagation)
We make preliminary investigations on a new approach to reducing radar cross section (RCS) of conducting objects. This approach employs novel planar metasurfaces characterizing nonuniform distribution of reflection phase. The operation principle of this approach and the design rule of the associated metasurfaces are explained using a simplified theoretical model. We then present a design example of such metasurfaces, in which three-layer stacked square patches with variable sizes are utilized as the reflecting elements. The proposed RCS-reduction approach is verified by both numerical simulations and measurements on the example, under the assumption of normal plane wave incidence. It is observed that, in a fairly wide frequency band (from 3.6 to 5.5 GHz), the presented example is capable of suppressing the specular reflections of conducting plates significantly (by more than 7 dB) for two orthogonal incident polarizations.